Risk factors for temporomandibular disorders: a systematic review of cohort studies - Da-Cas, Cecília Doebber (2024)
Objective: A systematic review was performed to synthesize and identify risk factors involved in TMD onset. Study Design: Electronic searches were conducted in PubMed, Web of Science, Scopus, Embase, PsyInfo and Lilacs databases, as well as in three gray literature databases (Google Scholar, ProQuest and Open grey). The studies were blindly assessed by two reviewers and selected by a pre-defined eligibility criterion. Risk of bias of included studies was assessed using the Joanna Briggs Institute Critical Appraisal Checklist for Cohort Studies. Grading of Recommendations Assessment, Development and Evaluation (GRADE) was evaluated for most related factors. Results: Twenty-one cohort studies were included. Significant factors were female gender, symptoms of depression and anxiety, perceived stress, sleep quality, symptoms of obstructive sleep apnea and presence of any comorbidity, such as Irritable Bowel Syndrome, lower back pain, headache frequency, tension-type headache, migraine and mixed headache. Moreover, high estrogen and low testosterone levels in utero, greater pain perception, jaw mobility pain, pain during palpation, orofacial anomalies, as well as extrinsic and intrinsic injuries were also significant. Conclusions: Several factors seems to be involved in TMD onset, however, more studies with standardized methodology are necessary to confirm these findings.